A Dryer performance model for a lateral-flow forced convection tray dryer in drying of sweet potato chips - Lijauco, Leonell P.; Quiros, Edwin N.; De Leon, Rizalinda (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Sweet potato Ipomeoa batatas L.) is an important source of carbohydrate for people in Asia including the Philippines.Since its root part is rich in B-carotene,food fiber,and potassium ion,etc.,researchers investigated its capabilities in using it as an ingredient to many types of food products.Drying is an essential process in producing products wherein researchers produced mechanical dryers to eradicate the disadvantages of the traditional sun drying which includes the reduction of time consumption,avoids the dependency on the weather,reduces microbial contamination of the product and lowers the product mass and volume which improves the efficiency of packaging,storing and transportation.Small dryers are particularly tray-type that are available only from Europe and the USA.Developing countries like the Philippines see the cost unaffordable and uneconomic for producers,so they developed a tray-type dryer intended for sweet potato chips where it was made of trays held in a cabinet and connected to a source of air heated by electricity.The air enters the bottom of the chamber below the trays and then rises,through the trays of food being dried,and exits from an opening in the top of the chamber.It was observed that drying was not uniform wherein the tray at the bottom dried faster than the top most tray.This study was conceptualized,and was therefore conducted to achive the desired uniform drying than the existing one.The moisture ratio data MR=f(t) obtained from the drying experiments of sweet potato chips were fitted to 5 mathematical models-Newton,Page,Henderson and Pabis,Simplified Fick's Diffusiion,and Modified Page.The values of the correlation coefficient (R2),the reduced chi-square (X2) and the root mean square error (RMSE) for different air temperature (40C,50C and 50C) and air blower velocity (14.336 m/sec,15.724 m/sec, and 17.212 m/sec) were determined using Non-Linear Estimation Analysis.Among the models considered,the Page and Modified Page models gave values of R2 above 0.99616.These models appear then the most adequate in describing the drying processes of sweet potato chips under the experimental conditions studied.The samples produced from the drying experiment of sweet potato chips were used for the sorption isotherm experiment.The dried sweet potato chips for temperature 40C of sorption experiment came from the treatment 40C and 17.212 m/sec air velocity;50C samples came from the treatment 50C and 17.212 m/sec air velocity;50C samples came from the treatment 50C and 17.212 m/sec air velocity;50C samples came from the treatment 50C and 17.212 m/sec; and 60C samples came from the treatment 60C and 17.212 m/sec air velocity.The sorption data were fitted to five well-known sorption isotherm equations-Modified Henderson,Chung-Pfost,Modified Halsey,Modified Oswin and Guggenheim-Anderson-de Boer (GAB) equations.However,40C and 50C treatments fitted on Modified Oswin while 60C on Chung-Pfost.The sorption data were also fit to GAB model and it gave a perfect value of 1.0 for R2.But, the parameters of GAB model consider only the effects of relative humidity and moisture content.
Thesis (Ph.D. Energy Engineering)--University of the Philippines Diliman
Keywords: Sweet potatoes -- Drying; Sweet potatoes -- Philippines; Food -- Drying -- Equipment and supplies